Narrative elements in Abdul-Wahab al-Bayati poetry - farhad Rajabi; Shahram Delshad; Shahram Delshad (دراسات فی اللغه العربیه و آدابها)
Poems and stories have traditionally interacted. We find poets who told stories in their poetry. As the genre of story was not common in Arabic literature, Arab poets used it in their poems. Hover, in spite of the prevalence of stories in modern literature, narrative poetry has been used as a way of poetic expression by poets. Free Arabic poetry and modern Arabic poetry, unlike traditional poetry, which based on monologues, have a dramatic structure, as it encapsulate a collective spirit. Such structure is in need of narration to be in harmony with the collective spirit. This is the reason why such stories have grasped the attention of modern poets. One such poet is Abdulwahab al-Bayati, who was interested in dramatic poetry and odes. So we find narrative features in his poetry and the stories are derived from history, literature and mythology. In this study, we investigate narrative elements in the poetry of Abdulwahab al Bayati. We focus on four famous odes by him. The goal of the study is a qualitative and analytical exploration of narrative elements.